LEXICAL MEANS OF INFLUENCE IN POLITICAL TEXT: GENRE OF SPEECH - Tsvirkun, T. (Linguistic and Conceptual Worldviews, 2020)
Language in the modern world allows not only inform, communicate, report something. It not only helps to understand the world and serves as a means of expressing feelings, transmitting impressions, but also a means of influence on recipients. In the present conditions of human development, the influence in different spheres of society is extremely important and relevant, and especially in political sphere of existence of any country. It is extremely important that success of modern politicians and leaders of the country depends mainly not on their power but on a word that can be successfully and appropriately selected and by doing so, influence the recipients: focus on something that will attract the attention on the audience, emphasize on something with the right words selected, not only more accurately and successfully convey information but reproduce exactly the information that will have an impact on the recipients etc. The it has been investigated in the political text including one of its genres of speech. research concerns the first speeches of Presidents of Ukraine Volodymyr Zelenskiy and Petro Poroshenko at the general debates of the UN General Assemblies in 2015 and 2019 respectively. Analysis of the very first speeches of the Presidents, proclaimed at the international level during the gathering of representatives of different countries at the general debates of the United Nations was driven by the fact that it is from the first speeches that the president’s image and the image of his country and citizens begin to be formed. Research made it possible to follow the common and the different features of using terms in the secondary nomination, handing facts using numbers of different structures, service of forms of the highest degree of expression of emotions, use of stories, quotes and extremely important words-values for the Ukrainian people in political texts of both Presidents.
Keywords: influence, political text, speech, lexical means, means of influence